Peningkatan keterampilan dan motivasi guru dalam merancang pembelajaran matematika berbasis proyek dan penguatan pendidikan karakter - Awi Dassa; Said Fachry Assagaf; Muhammad Husnul Khuluq (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
This program aims to improve teachers’ skills and motivations in designing project based learning (PjBL) integratedwith character education (PPK) in their mathematics class. The activity was set in a workshop involving mathematics teachercouncils (MGMP) in Gowa regency. The agenda was divided into three, namely, 1) introduction to PjBL and PPK, 2) designingPjBL integrated with PPK in mathematics learning, and 3) socialization of scientific article publication of design implementationby teachers. Within this activity, the teachers-participants have succesfully presented seven designs of PjBL integrated with PPK,indicating their improved skills in the related aspect. In addition, reflection questionnaire shows 90.47% of the teachers believedif they could present and are willing to conduct PjBL integrated with PPK in their class. This shows a significant improvement inteachers’ motivations which was in the low category. Following this program, observations to teachers’ implementation of thedesigned lesson plan and coaching in publishing their implemented learning designs would be suggested to conduct.